Will in Extreme Emergency: Philosophical-Legal Analysis and Proposal for Exceptional Regulation in Peruvian Law - Marco Antonio Corcuera Garcia; Norma Lisbeth Quezada Salirrosas (Universidad Ciencia y Tecnología, 2025)
In this paper, the philosophical and legal foundations that support the need to establish a special will applicable in situations of extreme emergency were identified. To this end, deductive, inductive and analytical methods were used, using interview and bibliographic analysis as techniques. The most significant finding reveals that the current regulatory framework considerably limits the possibility of granting a will in emergency contexts, mainly due to requirements such as the physical presence before a notary and the handwritten drafting of the act. These requirements represent barriers that prevent the expression of the last will. This affirms that there are solid foundations to implement a special testamentary form, therefore, it is proposed to replace traditional mechanisms with technological tools, such as digital signature and videoconferencing, that guarantee the validity and security of the testamentary act in critical scenarios.